2019
DOI: 10.3168/jds.2018-14565
|View full text |Cite
|
Sign up to set email alerts
|

Individual and sequential effects of stirring, smoothing, and cooling on the rheological properties of nonfat yogurts stirred with a technical scale unit

Abstract: Few studies have considered the impact of unit operations during stirred yogurt manufacture because their operational sequence is difficult to replicate at the laboratory scale. The aim of this study was to investigate the individual and sequential effects of stirring in the yogurt vat, smoothing, and cooling on the rheological properties of yogurts, using a technical scale unit simulating some industrial conditions. The yogurts were prepared from a milk mixture that was standardized to contain 14% total solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
0
19
0
3
Order By: Relevance
“…When the yogurt was stirred at 42°C, induced syneresis was highest (Figure 3); significantly lower values were found for YR and Y20. In a study by Guénard-Lampron et al (2019), no differences in induced syneresis were observed, whether the yogurt was smoothed at 38°C or 20°C. In that study, the contribution of each unit operation (stirring, pumping, smoothing, and cooling) to the total change in induced syneresis (as a percentage) was determined.…”
Section: Yogurt Gel Propertiesmentioning
confidence: 89%
See 2 more Smart Citations
“…When the yogurt was stirred at 42°C, induced syneresis was highest (Figure 3); significantly lower values were found for YR and Y20. In a study by Guénard-Lampron et al (2019), no differences in induced syneresis were observed, whether the yogurt was smoothed at 38°C or 20°C. In that study, the contribution of each unit operation (stirring, pumping, smoothing, and cooling) to the total change in induced syneresis (as a percentage) was determined.…”
Section: Yogurt Gel Propertiesmentioning
confidence: 89%
“…The steps in the yogurt stirring operation are also known to affect gel functionality. Afonso and Maia (1999) and Guénard-Lampron et al (2019) found that the smoothing and cooling step performed with a plate heat exchanger was responsible for major changes in viscosity, elasticity, and firmness throughout the process. Moreover, when the gel was smoothed at 38°C versus 20°C, the yogurts were firmer (Guénard-Lampron et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…El uso de estabilizantes puede ayudar a proporcionar una consistencia más uniforme. Sin embargo, puede haber defectos de textura relacionados con el uso de estabilizantes, incluida la estabilización excesiva (sobre estabilización) que da como resultado un yogur elástico "gelatinoso", lo que puede generar una separación débil del cuerpo o del suero "líquida" (Vedamuthu, 1991), lo que ocasionan un efecto negativo en las propiedades físicas y sensoriales del producto (Guénard-Lampron, St-Gelais, Villeneuve, & Turgéon, 2019).…”
Section: Introductionunclassified
“…Product texture is of outstanding importance for consumer acceptance and affected by, for example, fat content reduction as a response to consumer demands for low‐fat products (Lucey & Singh, ). To improve texture different strategies can be applied, including changes in processing (Guénard‐Lampron, St‐Gelais, Villeneuve, & Turgeon, ), or the incorporation of additional protein or commercial thickeners (Loveday, Sarkar, & Singh, ). As an alternative, mesophilic or thermophilic lactic acid bacteria with the ability to produce extracellular polysaccharides (EPS) are increasingly used in the dairy industry.…”
Section: Introductionmentioning
confidence: 99%